IMPLEMENTASI KEBIJAKAN PERATURAN MENTERI PENDIDIKAN NASIONAL REPUBLIK INDONESIA NOMOR 78 TAHUN 2009 TENTANG PENYELENGGARAAN SEKOLAH BERTARAF INTERNASIONAL PADA JENJANG PENDIDIKAN DASAR DAN MENENGAH DI SMA NEGERI 1 KUDUS - Hesti Annisa; Hartuti Purnaweni; Dewi Rostyaningsih (Journal of Public Policy and Management Review, 2013)
SMA 1 Kudus was RSBI (Pre International Standardized School) since 2007. One of the school requirements of RSBI to become SBI (International Standardized School) is the fulfillment of pre requirement standard stated in the Permendiknas No.78/2009. This study attempted to answer the implementation of Permendiknas No.78/2009 on International Standardized School in Elementary and Secondary Education, at SMA 1 Kudus. This research focused on the implementation of nine standards of quality education stipulated in the regulation, at SMA 1 Kudus, as an effort of this school to reach SBI status.This research used qualitative research method, to describe phenomenon that affect the implementation of Permendiknas No.78/2009 based on nine standards of quality education, namely: Accreditation, Curriculum, Learning Process, Value, Educator, Staff of Education, Infrastructure, Management, and Cost. From the result of research, it is known that the implementation that have been well done based on the nine standards of quality education are: Curriculum, Value, Staff of Education, Infrastructure, Management, and Cost. However, Accreditation, Learning Process, and Educator have not been well implemented, because lack of human and financial resources.Recommendations from the results of this research in order to improve the implementation of Permendiknas No.78/2009 is that SMA 1 Kudus should encourage its teachers to get their graduate education, and to make cooperation with local government for fund allocation for the betterment of SMA 1 Kudus.